Stellarator fusion systems enabled by arrays of planar coils - D.A. Gates; S. Aslam; B. Berzin; P. Bonofiglo; A. Cote; D.W. Dudt; E. Flom; D. Fort; A. Koen; T.G. Kruger; S.T.A. Kumar; M.F. Martin; et al. (Nuclear Fusion)
We present an overview of a novel electromagnetic coil configuration for stellarators and its application to two near-term fusion systems. The novel coil configuration is the planar coil stellarator, able to implement precisely-quasisymmetric 3D magnetic fields using a set of planar, plasma-encircling coils and a set of planar, field-shaping coils situated on a surface surrounding the plasma. This configuration combines the stellarator’s advantages of steady-state operation, stability, low recirculating power fraction, and a mature physics basis, with the benefits of using simpler, planar coils which allow for a maintenance scheme leveraging large ports, and the ability to control magnets individually. The initial near-term use case considered is a steady state deuterium–deuterium stellarator neutron source, called Eos. The second near-term use case considered is a deuterium–tritium stellarator fusion pilot plant, called Helios, that would be approximately twice the linear dimension of the Eos design.